Spreadsheet application in partial differential equations - Tan, Chen Hong. (2011)
This project is serving as a learning text to numerical methods of solving partial differential equations. The numerical methods covered here are commonly included in most engineering and science subject. They are the Elliptic, Hyperbolic and Parabolic equation.The program is developed using excel spreadsheets. The spreadsheet will is select, because it a simple tool for both analyzing physical problems modeled and enhancing the learning curve. The user does not need to understand all the functions of the Excel, but still able to use the Spreadsheet. And as excel is a very common software, most user will be very familiar with it. The program need to be able the user to input data, and provide the user with solution. The program also will provide graph to give user a better picture of the solution.